Focused ion beam nanoscale patterned transmission-enhanced fiber-optic tips - Wang, Houxiao (2014)
The angled and tapered antireflection and transmission-enhanced fiber-optic tips were designed, fabricated, and characterized based on nanoscale surface modification using the nano-precision focused ion beam (FIB). The developed optical fiber tips showed combined functions of antireflection and transmission enhancement for higher detection efficiency or signal-to-noise ratio because the FIB-milled nanoholes into the fiber tip endfaces could act as tapered air-filled nanopillars, changing the light propagation direction, enhancing the scattering effect, and allowing more photons to transmit along/near the glass/air interface to enhance the local evanescent field for sensing/detection.